2013
DOI: 10.5694/mja12.11241
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care for men diagnosed with prostate cancer in Victoria from 2008 to 2011

Abstract: • 28,405 Victorians were diagnosed with cancer 1 and 10,631 died from cancer in 2011.• The most common new cancers were prostate, breast, bowel, and lung cancers and melanoma.• The leading cancers for mortality were lung, bowel, prostate, breast and pancreatic cancers. NumbersEach year, over 28,000 Victorians develop cancer, other than one of the common skin cancers 1 , and over 10,500 deaths are caused by it. In 2011, 15,695 men and 12,710 women presented with new cancers and 5,921 men and 4,710 women died fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 14 publications
3
96
5
1
Order By: Relevance
“…The PCR also includes the Expanded Prostate Cancer Index Composite (EPIC) questionnaire at 12 and 24 mo. As of late 2014, it had enrolled >10 000 patients and has led to significant publications reporting patterns of care [42], positive surgical margins [43], and the use of active surveillance [44]. As a result, this Melbournebased registry has been awarded a grant by the Movember Foundation to extend its reach by creating a national PCa registry for Australia.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR also includes the Expanded Prostate Cancer Index Composite (EPIC) questionnaire at 12 and 24 mo. As of late 2014, it had enrolled >10 000 patients and has led to significant publications reporting patterns of care [42], positive surgical margins [43], and the use of active surveillance [44]. As a result, this Melbournebased registry has been awarded a grant by the Movember Foundation to extend its reach by creating a national PCa registry for Australia.…”
Section: 3mentioning
confidence: 99%
“…Guideline adherence for radiographic staging of men with newly diagnosed PCa [133] Implementation of novel clinical pathways to address fluoroquinolone resistance and infectionrelated hospitalizations among men undergoing prostate biopsy [134] Implementation of performance feedback and collaborative-wide educational activities to improve documentation of clinical TNM stage in PCa patients [135] Variation in the use of active surveillance for men with low-risk PCa [ Contemporary patterns of care for men newly diagnosed with PCa [42] Positive surgical margins: rate, contributing factors and rate of additional therapy [43] Active surveillance patterns of care in a contemporary PCa registry [44] RP = radical prostatectomy; ADT = androgen deprivation therapy; EAU = European Association of Urology; CAPRA = Cancer of the Prostate Risk Assessment; PSA = prostate-specific antigen.…”
Section: Caesar: Comparative Effectivenessmentioning
confidence: 99%
“…However, a state-wide patterns of care study found that in New South Wales (NSW), Australia's most populous state with 7.4 million inhabitants, less than 10% of men with locally advanced prostate cancer receive adjuvant radiotherapy within the recommended timeframe [13]. These figures are consistent with data from other regions of Australia [14,15] and the United States where recent analyses indicate only 10-20% of qualifying patients receive adjuvant radiotherapy [16][17][18][19].…”
Section: Introductionmentioning
confidence: 63%
“…Australian data indicates that 92% of men diagnosed with prostate cancer are alive five years later [5]. Recently published Victorian data demonstrate that the vast majority of men (93%) are diagnosed with localised disease and three quarters have low-or intermediate-risk disease [6]. Of those with low-or intermediate-risk disease, three-quarters will seek some form of active treatment in the initial 12 months post diagnosis.…”
Section: Introductionmentioning
confidence: 99%